CHALLENGES OF THE INTERFERENCE IN TEACHING FUTURE INTERPRETERS - TSARYK, Olga; RYBINA, Nataliia (HUMANITARIAN STUDIES: HISTORY AND PEDAGOGY, 2021)
Annotation. The article examines the problems that arise in the process of learning foreign languages by future translators, in particular the phenomenon of linguistic interference in oral and written speech. The aim of the work is to identify the peculiarities of overcoming linguistic interference in the process of teaching students by analyzing the causes of this phenomenon and effective methods of avoiding it. Based on the analysis of scientific works, it is established that interference can be viewed from three different points of view: as a result of the interaction of two or more systems, as a process of this interaction and as prerequisites for it. It is emphasized that no languages interact by themselves as language systems, i.e., interference occurs in a certain social group, and the preconditions for certain processes and results of interference are largely determined by the properties of the members of this group. The authors used the methods of monitoring students studying English, German and Ukrainian as foreign languages, as well as the analysis of informants involving teachers of Ukrainian, German and English. Based on the results of observations of foreign and Ukrainian students studying a foreign language, the phonetic conditionality of phonological processes is established, which is manifested in the absence of a difference between the sounds of the native and foreign languages - possible errors are determined by the sensory and perceptual characteristics of the speaker; and with an adequate perceptual assessment, correct realization may stop working due to the influence of the properties of the articulation base of the native language - errors are of a motor nature. The article deals with orthographic, grammatical (morphological, syntactic and punctuation), lexical, semantic, stylistic and intra-linguistic interference. Orthographic interference is the negative influence of similar words in another language on the spelling of words in one language. The influence of the grammatical structure of the native language on the second language of a bilingual is manifested in mixed case values, in the function of prepositions, in the violation of word order, inconsistency of genders, numbers and cases. Lexical interference is defined as the borrowing of foreign language lexemes during bilingualism, which is expressed either in the transfer of phonemic sequence from one language to another, or in the violation of the structure of the meaning of a native language lexeme or in formations modeled on foreign language words. Semantic interference is manifested at the level of word meaning. It is emphasized that in case of incorrect choice of a particular language situation, it is a stylistic interference.